Burdens of gastric and colorectal cancers and their attributable risk factors among 31 countries and territories in the Western Pacific region, 2000-2021 - Liangyu Kang; Wenxin Yan; Wenzhan Jing; Ning Zhang; Min Liu; Wannian Liang (The Lancet Regional Health. Western Pacific)
Background: Stomach cancer (SC) and colorectal cancer (CRC) are two leading gastrointestinal cancers worldwide, with particularly heavy burdens in the Western Pacific region (WPR). This study aimed to comprehensively describe the regional landscape, temporal trends, and risk factors for the burdens of SC and CRC in the WPR. Methods: Estimates of incidence, disability-adjusted life years (DALYs), and deaths for SC and CRC were obtained from the Global Burden of Disease Study 2021. We calculated the percentage of relative changes in incident cases, DALYs, and deaths between 2000 to 2021. Estimated annual percentage changes (EAPCs) were used to reflect trends of age-standardized incidence rates (ASIR), age-standardized DALY rates (ASDR), and age-standardized mortality rates (ASMR). Risk factors for SC and CRC were also presented. Findings: In 2021, the numbers of incident cases of SC and CRC were 756,303 and 933,200 in the WPR, constituting 61.77% and 43.07% of the global totals, respectively. From 2000 to 2021, the ASIR (EAPC=-2.30, 95% CI -2.44 to -2.16), ASDR (EAPC=-3.41, 95% CI -3.59 to -3.23), and ASMR (EAPC=-3.11, 95% CI -3.29 to -2.94) of SC decreased. Despite the increase in incident cases (24.00%) and deaths (8.33%) of SC, the DALYs declined by 6.20%. The ASIR of CRC increased by an average of 1.32% (95% CI 1.25% to 1.39%), while ASDR (EAPC=-0.48, 95% CI -0.59 to -0.38) and ASMR (EAPC=-0.45, 95% CI -0.53 to -0.37) declined. China exhibited the highest numbers of incident cases, DALYs, and deaths for both cancers among the 31 WPR countries or territories. Although the ASDRs of SC decreased in 27 countries, an increase was detected in Guam. Meanwhile, Viet Nam showed the fastest increase in ASIR of CRC, followed by China and Philippines. The incident cases, DALYs, and deaths of both SC and CRC peaked in individuals aged 65-74 years. The rates of incidence, DALY, and mortality increased non-linearly with age and were generally higher in males than in females. The slowest decline in incidence rates of SC (EAPC=-0.50, 95% CI -0.80 to -0.20) and the fastest increase in incidence rates of CRC (EAPC=2.57, 95% CI 2.19 to 2.95) were observed among individuals aged 25-29 years. The rates of DALY and mortality for both cancers decreased slowly or even increased among the elderly over 80 years. Smoking and diet high in sodium were attributable to 59.66 and 36.16 DALYs of SC per 100,000 population in 2021. Diet low in milk, diet low in whole grains, and diet high in red meat were three leading risk factors for DALYs and deaths of CRC. There were increasing trends in the ASDR and ASMR of CRC due to high body-mass index and alcohol use (EAPC range: 0.54-1.97). Interpretation: SC and CRC remain noticeable public health issues in the WPR. There is a critical need to address the early onset of both cancers and improve management and prognosis for the elderly. More attention should be paid to smoking, alcohol use, and some dietary risk factors. Future research should focus on cost-effective screening and interventions to reduce the burdens of SC and CRC in WPR.